Analysis of the Correlation Between Anxiety Levels and the Performance of Wushu Taolu Athletes in the Qualifying Round of the 2026 Central Java Provincial Sports Championships - Diva Melani Putri; Dewi Anggraeni; Iqbal Indra Awaludin (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2026)
Anxiety levels can affect an athlete’s performance, particularly in sports like wushu taolu, which demand concentration, technical precision, and emotional stability. The Qualifying Round of the XVII/2026 Central Java Provincial Sports Week (PORPROV) Wushu Taolu is a high-pressure competitive event because it determines athletes’ advancement to the next stage, thereby potentially increasing anxiety before competition. This situation can lead to a decline in performance if not properly managed. This study was conducted to examine the correlation between anxiety and the performance of wushu taolu athletes in provincial-level competitions. This study employed a descriptive quantitative method using a correlational approach and a cross-sectional design. The sample consisted of 49 respondents selected through purposive sampling. Anxiety was measured using the CSAI-2R, and performance was based on judges’ scores. Data analysis was performed using the nonparametric Spearman’s rank correlation test with the assistance of SPSS version 30. The results showed that the athletes’ anxiety levels were in the low category (10%), moderate category (76%), and high category (14%). Meanwhile, athletes’ performance was categorized as low (11%), moderate (56%), and high (33%). The Spearman Rank correlation test yielded a correlation coefficient of 0.642 with a significance level of p < 0.001, indicating a strong relationship between anxiety levels and the performance of wushu taolu athletes. There is a significant correlation between anxiety levels and the performance of wushu taolu athletes. This relationship is positive, meaning that an increase in anxiety is followed by an increase in performance during competitions.